The Relationship between Research and Teaching: A Meta-Analysis - Hattie, John; Marsh, Herbert W. (Review of Educational Research, 1996)
A review of various relationship between research and teaching in universities is presented, and the evidence necessary to assess each model is outlined. A meta-analysis of 58 studies demonstrates that the relationship is zero. Suggestions for future directions are provided, and it is argued that a major goal coulds be to adopt strategies that enhance the relationship between research and teaching.